2023
DOI: 10.1186/s12879-022-07965-4
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of tuberculosis and susceptibility to antituberculosis drugs in Reunion Island

Abstract: Background Tuberculosis is the first fatal infectious agent in the world with 1.2 million annual deaths for 10 million cases. Little is known about the epidemiology of tuberculosis and its resistance in Reunion Island, which is at the heart of migratory flows from highly endemic Indian Ocean territories. Methods We carried out a retrospective observational study of cases of tuberculosis disease in Reunion Island between 2014 and 2018. The epidemiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Only primary quantitative studies were selected from the search output. The title of the study, year of study, study setting, study design, MDR-TB confirmed number of cases, MDR-TB/HIV co-infection proportion, and the outcome explored were characteristics retrieved from the studies (Table 1 ) [ 9 13 , 14 ▪▪ , 15 21 , 22 ▪▪ , 23 , 24 ▪▪ , 25 29 , 30 ▪ , 31 ▪ , 32 36 , 37 ▪▪ , 38 48 , 49 ▪▪ , 50 ▪ ].…”
Section: Search Methodsmentioning
confidence: 99%
“…Only primary quantitative studies were selected from the search output. The title of the study, year of study, study setting, study design, MDR-TB confirmed number of cases, MDR-TB/HIV co-infection proportion, and the outcome explored were characteristics retrieved from the studies (Table 1 ) [ 9 13 , 14 ▪▪ , 15 21 , 22 ▪▪ , 23 , 24 ▪▪ , 25 29 , 30 ▪ , 31 ▪ , 32 36 , 37 ▪▪ , 38 48 , 49 ▪▪ , 50 ▪ ].…”
Section: Search Methodsmentioning
confidence: 99%